LGBTQ+ Affirmative Psychological Interventions A Latine/x Perspective - Chaparro, Reynel Alexander; Abreu, Roberto L. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents descriptions of interventions, results of empirical research, and theoretical contributions developed by Latine/x psychologists based on affirmative approaches aimed at promoting acceptance and understanding of LGBTIQ+ people. Contributions in this volume bring together the work of Latine/x scholars, practitioners, and activists across five Latin American countries or territories (Argentina, Chile, Colombia, Mexico, and Puerto Rico) and in the United States, in an effort to provide multicultural perspectives to LGBTIQ+ affirmative psychological interventions that highlight local, regional and national particularities. Chapters in this volume go beyond contributions made by applied psychology fields (e.g., clinical and counselling psychology), where affirmative orientations are predominantly located, and include contributions from other fields of psychological research such as social and community psychology. The book is divided in two parts. Chapters in the first part focus on the experiences of trans and gender non-conforming people, with emphasis on contemporary systemic issues that affect gender identity among Latine/x communities and those who do not conform to hegemonic narratives about gender. Chapters in the second part focus on sexual identity among Latine/x LGBTIQ+ people and their families and communities. Contributions in this part present discussions about sexual orientation (grouped in LG/LGB identities), sex and gender dissidence, and the inclusion of intersex. LGBTQ+ Affirmative Psychological Interventions: A Latine/x Perspective will be of interest to both researchers and practitioners in different fields of psychology - such as clinical, counselling, social, and community psychology - interested in a multicultural perspective to understand and develop LGBTQ+ affirmative actions to fight against the repathologization of individuals, groups, families and diverse communities.
Chapter 1. Contemporary Latine/x LGBTIQ+ affirmative psychological interventions. An introduction -- Part 1: Experiences of Trans and Gender Non-Conforming People Among Latine/x Communities -- Chapter 2. Psychotherapy and Affirmative Practices with trans and gender non-conforming (TGNC) patients in Chile -- Chapter 3. Systematization of the experience of working with Trans women: Tensions between research and transformation -- Chapter 4. The body as psychic materiality. Spaces of reflection with gender nonconforming people -- Chapter 5. Between social rejection and gender reaffirmation: an approach to the narratives of trans women in Colombia -- Chapter 6. Research on coping with stress due to prejudice in transgender people: Some neglected aspects and new ideas -- Part 2: Sexual Identity Among Latine/x LGBTIQ+ People and their Families and Communities -- Chapter 7. Resources and barriers perceived by mothers, fathers, and gay and lesbian youth in the process of coming out in Cali-Colombia -- Chapter 8. Intersectional and Affirming Psychological Interventions for LGBTQ+ Latinx at risk of or living with HIV/AIDS -- Chapter 9. Design, implementation and evaluation of LGB affirmative care program for students and psychology professionals in Bogotá - Colombia. Testing research and training on LGB attitudinal change in psychologist -- Chapter 10. Psychopathologization of sex-gender dissidence and psychosocial action in Mexico: Towards an affirmative psychopolitics -- Chapter 11. LGBTQI+ Research and Affirmative Psychological Interventions in Puerto Rico.
Keywords: Sex (Psychology).; Counseling; Clinical psychology; Community psychology; Mental health; Psychology of Gender and Sexuality; Counseling Psychology; Clinical Psychology; Community Psychology; Mental Health